Trends in Moisture Index, Farmland Area, and Their Combined Effects on Grain Production in Northern China. (20th March 2014) - Lu, Qingshui; Gao, Zhiqiang; Xu, Xinliang; Ning, Jicai; Bi, Xiaoli
Abstract : China policies and Grain-for-Green Project have led to changes in farmland area and grain production. Climate change was also occurring during this period. To analyze the effects of land use and climate change on grain production, the area of farmland in northern China during 1988–2008 was determined from remote sensing images, a moisture index (MI) was calculated from daily meteorological data obtained from weather stations, and unit grain production was obtained from statistical yearbooks. Using statistical and spatial analyses, we determined that MI decreased across most of the study area during this period. This decrease in humidity caused humid zones to decrease and semiarid areas to increase. Combined effects of decreased humid area and conversion of farmland resulted in a decrease in agricultural land in humid areas and an increase in semiarid and arid areas. Increases in unit grain production, machine power, and irrigated farmland area led grain production to increase from 122, 799, 081 to 188, 532, 597 ton in humid areas, from 28, 875, 900 to 115, 976, 814 in semiarid areas, and from 7, 622, 100 to 15, 490, 026 in arid areas, respectively. Increased unit grain production and farmland resulted in increased importance of semiarid areas for grain production.